Echocardiographic Monitoring of Intracardiac Hemodynamics in Neonatal Respiratory Distress Syndrome - S. A. Perepelitsa; A. M. Golubev (Общая реаниматология)
Objective: to perform an early neonatal ultrasound study of intracardiac hemodynamics in premature neonates with respiratory distress syndrome (RDS) during mechanical ventilation. Subjects and methods. The paper presents the results of ultrasound study of intracardiac hemodynamics in 51 premature neonates. Two patient groups were identified. Group 1 comprised 34 infants with severe RDS who received the exogenous surfactant Curosurf and Group 2 consisted of 17 apparently healthy premature newborn infants. Results. Functional tension of the cardiovascular system was characterized for premature neonates with RDS. There were signs of left ventricular systolic dysfunction within the first 24 hours of life and those of right ventricular dysfunction by day 5 of postnatal age. Within 5 days of life, there were echocardiographic signs of pump dysfunction of both ventricles: stroke volume, cardiac index, and blood minute volume. Analysis of changes in peak blood flow velocity and peak pressure gradient across the atrioventricular valves of the right and left ventricles indicated that 17.6% of the children showed increases in peak blood flow velocity and tricuspid valve pressure gradient in the systolic phase. The greatest peak blood flow velocity changes were recorded in the pulmonary artery trunk. By day 5 of life, signs of pulmonary hypertension concurrent with hydropericardium remained in 29.4% of cases. RDS – was shown to be accompanied by higher Qp/Qs ratio in premature neonates. The lower index was attended by the alleviated signs of respiratory failure. In RDS, mainly left-to-right blood shunt was accomplished through the open oval window, but the shunt intensity decreased when the pathological process was resolved in the lung. The functioning patent ductus arteriosus was hemodynami-cally significant in none case. Conclusion. The premature neonates with RDS were found to have intracardiac hemo-dynamic changes. By day 5 of postnatal age, there was no normalization of major intracardiac hemodynamic parameters although respiratory failure resolved in most neonates. Key words: premature neonates, respiratory distress syndrome, mechanical ventilation, intracardiac hemodynamics, echocardiography.